Gender and Economic Growth Assessment for Ghana 2007 - Agboli, Mary (International Finance Corporation, Washington, DC, 2017)
This study presents an assessment of the role of gender in economic growth in Ghana with emphasis on constraints to enterprise operations, investment, and growth among women owned firms. Anecdotal evidence suggests that women own up to a third of businesses in Africa, and that this represents a significant source for scaling up economic growth in such countries. In Ghana, women make up about 50.1 percent of the entire labor force and are mostly involved in micro enterprises and the retail trade. In spite of the fact that gender issues in Ghana have been given significant attention over the last decade in particular; and that Ghana ranks relatively well in terms of gender equity, there remains a number of legal, administrative, and institutional barriers that impede the growth of women-owned businesses and for that matter women in general to attain their full potential. This report was undertaken for the Ministry of Women and Children’s Affairs (MOWAC) and coordinated by the International Finance Corporation (IFC’s) Private Enterprise Partnership for Africa under the gender-entrepreneurship markets initiative. The study was conducted between July and November 2006. Most economically-active women in Ghana operate in the informal economy and are mostly involved in micro-enterprises and retail trade. Women in the informal sector tend to be located in the poorer segments of the economy, particularly in food crop farming and the micro enterprises sector. The general legal framework for property rights and business formation in Ghana does not contain explicit provisions that inhibit women’s economic participation. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.